ORE MINERALS FROM KUROKO TYPE DEPOSIT OF TOYA-TAKARADA MINE, HOKKAIDO, JAPAN - Yuningsih, ST., MT., Ph.D, Euis Tintin (Buletin Sumber Daya Geologi, 2016)
Toya-Takarada mine is Au- and Ag-rich Kuroko-type deposit located in Takarada, Toya-mura, southwest Hokkaido, Japan. The deposits were hosted in rhyolitic tuff and mudstone of Middle Miocene age. Ore samples of fine-grained black ore, vuggy black-yellow ore, granular vuggy black ore, quartz-sulfide ore and massive quartz-barite ore were studied to identify the ore minerals association in the Toya-Takarada mine. The ore minerals are dominated by sphalerite, galena, chalcopyrite and pyrite with fewer amounts of electrum, tetrahedrite-tennantite, and other sulfosalt minerals with secondary mineral of covellite.The quantitative chemical analysis of ore minerals by EPMA indicated that FeS contents in sphalerite is low (0.3-1.2 mol.%) in all kinds of ore samples. Small grains of electrum as inclusions in pyrite are identified in vuggy black-yellow ore with Ag content around 32-33 atm %.In general, the silver minerals in Kuroko-type deposits occurred mainly in the black and yellow ores zone dominantly composed of sphalerite, galena, pyrite, chalcopyrite and barite as a form of electrum and/or argentian tetrahedrite-tennantite series. Thus, the massive quartz-barite ore sample of Toya-Takarada mine are also contain some rare silver sulfosalt minerals such as proustite, Cu-rich pearceite, geocronite-jordanite and fizelyite. Those minerals were found together in association with sphalerite. It seems that sphalerite was crystallized first followed by proustite and Cu-rich pearceite, then geocronite-jordanite and fizelyite are crystallized later.Sphalerites from quartz-sulfide ore of Toya-Takarada contain some fluid inclusions and measured homogenization temperatures are in the range of 164-247°C (av. 208°C) with salinity ranging from 1.9 to 4.7 wt.% NaClequiv. (av. 3.9 wt.% NaClequiv.). The mineral assemblage, iron content in sphalerite and silver content in electrum were indicated that sulfur fugacity was slightly higher during ore mineralization in Toya-Takarada mine.